2002
DOI: 10.1046/j.1439-0434.2002.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Aggressiveness andIn PlantaInteractions ofBotrytis cinereaand other Filamentous Fungi Quiescent in Grape Berries and Dormant Buds in Central Washington State

Abstract: Recovery of quiescent filamentous fungi from nonsymptomatic grape berries and dormant buds demonstrated dominance of Alternaria, Aureobasidium, Cladosporium, Ulocladium and other dematiaceous hyphomycetes. Up to 78% of berries contained fungi prior to harvest. Botrytis cinerea was recovered from 0.2 to 0.5% of surface-disinfested berries just subsequent to fruit set, and 1.6-4.8% of surface-disinfested, over-wintered dormant buds. In laboratory inoculations of mature grape berries with strains of Alternaria, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…As mentioned, we have isolated other fungal genera that have been reported to control grapevine pathogens, such as Alternaria (A. alternata, A. tenuissima and A. arborescens). Taxa from this cosmopolitan group have been previously characterized as endophytes of grapevine (Polizzotto et al 2008), and reported to inhibit etiological agents of grapevine diseases like Plasmopara viticola (Musetti et al 2006) or Botrytis cinerea (Dugan et al 2002). Furthermore, other "classical" fungal antagonists like those from the genus Trichoderma were also isolated in our study with a total of 44 isolates, including T. aureoviride and T. harzianum.…”
Section: Discussionsupporting
confidence: 60%
“…As mentioned, we have isolated other fungal genera that have been reported to control grapevine pathogens, such as Alternaria (A. alternata, A. tenuissima and A. arborescens). Taxa from this cosmopolitan group have been previously characterized as endophytes of grapevine (Polizzotto et al 2008), and reported to inhibit etiological agents of grapevine diseases like Plasmopara viticola (Musetti et al 2006) or Botrytis cinerea (Dugan et al 2002). Furthermore, other "classical" fungal antagonists like those from the genus Trichoderma were also isolated in our study with a total of 44 isolates, including T. aureoviride and T. harzianum.…”
Section: Discussionsupporting
confidence: 60%
“…They showed varying effectiveness at inhibiting the pathogen. Only A. alternata, a known grapevine endophyte (12,18,25), was completely effective in inhibiting P. viticola sporulation on grapevine leaf disks in these trials. For this reason, we conducted further studies on the interaction between the pathogen and A. alternata.…”
Section: Discussionmentioning
confidence: 84%
“…alternata is a cosmopolitan species and has often been reported to inhabit the structures of substomatic chambers (18,39). It is well known that the P. viticola mycelium develops first in the substomatal air space, which subsequently becomes almost completely invaded by the growing hyphae (22).…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria species are usually the principal fungal component of endophytic communities in phyllospheres, mostly due to their particular life style, producing highly melanised hyphae capable to resist and grow under intense UV radiations. Alternaria species (37 % of total isolates; 50 % in biological and 50 % in conventional), have shown antagonistic effects against Botrytis cinerea and grapevine downy mildew caused by Plasmopara viticola (Dugan et al 2002;Musetti et al 2006). The genus Epicoccum comprises 29 % of total isolates obtained in this study (average > 61 % in conventional mode).…”
Section: Discussionmentioning
confidence: 99%